PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MIND MAPPING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IX DI SMP NEGERI 17 KERINCI - Ainay Lizana (Jurnal Edukasi dan Penelitian Matematika, 2022)
Abstract – Mathematics learning outcomes are one indicator of the success of a learning process. However, based on observations, the MID score shows that the mathematics learning outcomes of Class VIII SMP Negeri 17 Kerinci students in the 2021/2022 academic year are still not good. One effort to overcome this is to use a mind mapping type of cooperative learning model. The purpose of this study was to describe and find out the learning outcomes of students who were taught by mind mapping cooperative learning model were better than students who were taught by conventional learning in class VIII of SMP Negeri 17 Kerinci. This study uses a static group design. Based on the analysis of related data, the researchers found that there was an effect where the learning outcomes of mathematics taught by applying the Mind Mapping Type Cooperative learning model were better than the learning outcomes of mathematics taught by direct learning models in class IX of SMP Negeri 17 Kerinci.Keywords– Mind Mapping, Mathematics Learning Outcomes, Cooperative Method